Perfil químico e dinâmica espacial e temporal de flavonoides de soja [Glycine Max (L.) Merr.] - Costa, Josicleia Oliveira (Universidade Federal de São Carlos, 2021)
The soybean (Glycine max) is a legume species originally from China, belonging to the Fabaceae family. This crop is exposed throughout its cycle to attack by different species of insect pests, which can affect the plant development and, consequently, its productivity. Some studies classify flavonoids as relevant constituents in the defense of soybean against injury to herbivores. Despite the potential role of flavonoids against herbivores, little is known about the variability and spatial and temporal allocation of these defenses in soybean leaves and throughout its developmental stages. Therefore, this work aims to investigate the chemical profile of a commercial soybean cultivar, comparing the flavonoid profiles from different leaves over different developmental stages. Conventional soybean seeds BRS 284 were germinated and grown in a greenhouse. Samples of old, young and immature leaves from emergency stage (VC), cotyledon stage (VE), vegetative stages 1, 2, 3, 4 and 5 (V1 to V5), and reproductive stages 1 and 2 (R1 and R2) were collected and extracted in 1:1 (v/v) methanol: water, and the extracts were analyzed by LC- MS. The main flavonoids of soybean leaves were identified by mass spectra and relatively quantified. During the developmental stages, higher levels of kaempferol mono, di and isomeric triglycerides found in immature and young leaves were found. The initial stages, emergency vegetative and coethylene vegetative, showed higher concentrations of isoflavones such as daidzein, genistein, glycitein and their glycoconjugates, which are more abundant in old leaves. The chemical profile and allocation dynamics of the studied flavonoids provide information on the different strategies used by the plant to allocate its resources, demonstrating that leaves of different ages differ in their composition, possibly according to their physiological and ecological context. Therefore, evidence of the role of constitutive flavonoids in the defense mechanism of soy will help in the development of methods that can contribute to agricultural productivity, adaptability and resistance to various stressors in a more sustainable way.
Chemical profile and spatial and temporal dynamics of soybean flavonoids [Glycine max (L.) Merr.]
Keywords: Soja; Flavonoides; Isoflavonas; Defesas; Metabólitos secundários; Soybean; Flavonoids; Isoflavones; Defenses; Secondary metabolites; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::QUIMICA DOS PRODUTOS NATURAIS